P1190OXIDATIVE STRESS AND INFLAMMATION IN PERITONEAL DIALYSIS: DANGEROUS AND TO BE SOLVED. (6th June 2020) - Innico, Georgie; Bertoldi, Giovanni; Alessi, Marianna; Pagnin, Elisa; Simeone, Monica; Baboci, Gresa; Bonfante, Luciana; Calò, Lorenzo
Abstract: Background and Aims: Cardiovascular disease is the leading cause of excess mortality in chronic kidney disease (CKD) and dialysis patients with oxidative stress (OxSt) and inflammation playing a pivotal role, as non-traditional risk factors and OxSt and inflammation have been shown to increase in peritoneal dialysis. Rho kinase (ROCK) activation is deeply involved in the induction of OxSt and inflammation and is closely linked to cardiovascular-renal remodeling. We aimed to evaluate in peritoneal dialysis patients with a molecular biology approach OxSt, in terms of phosphorylation state of MYPT-1 (marker of ROCK activity), the protein expression of p22 phox (subunit of NADPH oxidase, essential for the generation of ROS), and inflammation state, in terms of acute-phase proteins level (Interleukin 6 (IL-6), ultra-sensitive C-reactive protein (US-CRP), Ferritin, Albumin and Transferrin). Method: 9 male ESRD patients (39-81 years old) were enrolled and analyzed before (baseline) and after three and six months of peritoneal dialysis treatment (CAPD 7 patients, APD 2 patients). Mononuclear cells (PBMCs) MYPT-1 phosphorylation state and p22 phox protein expression were determined by Western Blot. Specific acute-phase proteins as IL-6, US-CRP, Ferritin, Albumin and Transferrin were assessed through blood chemistry tests. Results: MYPT-1 phosphorylation was increased after six months of treatment with peritoneal dialysis compared with three months and predialysis (1.03±0.07 vs 1.02±0.04 vs 1.57±0.16 d.u., p<0.0001). p22 phox protein expression (0.72±0.05 vs 0.73±0.10 vs 1.28±0.12 d.u., p<0.0001) and ferritin level (101.4±15.3 vs 173.6±11.5 vs 189.0±20.3 µg/l, p=0.002) increased as well. Albumin was decreased after six months of peritoneal dialysis treatment compared with three months and predialysis (43.38±0.10 vs 40.00±1.59 vs 36.46±1.43 g/l, p=0.007). IL-6 and US-CRP remained unchanged at a high level. Conclusion: The increase of OxSt and inflammation during peritoneal dialysis is confirmed also at molecular biology level and may lead in the medium-long term to dangerous consequences. The necessary improvement of OxSt status in peritoneal dialysis needs a multitarget approach. It might include the use of neutral pH, low glucose degradation products, low lactate and iso-osmolar peritoneal dialysis solutions, strict glycemic control, optimal volume management and, likely, a supplementation with antioxidants as N-acetylcysteine.